2013
DOI: 10.1016/j.addbeh.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Association between adolescent substance use and obesity in young adulthood: A group-based dual trajectory analysis

Abstract: Purpose This study investigated whether and how trajectories of substance use in adolescence were associated with obesity trajectories in young adulthood. We hypothesized that: (1) exposure to persistent substance use throughout adolescence may heighten obesity risk in young adulthood; and (2) such associations may differ once gender, ethnicity, socioeconomic status, and obesity status in adolescence, are considered. Methods The study included 5,141 adolescents from the child sample of the 1979 National Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 53 publications
4
54
0
1
Order By: Relevance
“…Prevalence of overweight or obesity in young adults from the Mater-University of Queensland Study of Pregnancy and its Outcomes was significantly lower in marijuana users in multivariate-adjusted analyses [9]. In contrast, a study using the National Longitudinal Survey of Youth found that, compared to nonuse or low use in adolescence, consistent or increasing patterns of marijuana use in adolescence are associated with an increased risk of obesity [10]. In another study among youth in the United States, frequent marijuana use was associated with overweight status but not obesity in young girls [11].…”
Section: Introductionmentioning
confidence: 69%
“…Prevalence of overweight or obesity in young adults from the Mater-University of Queensland Study of Pregnancy and its Outcomes was significantly lower in marijuana users in multivariate-adjusted analyses [9]. In contrast, a study using the National Longitudinal Survey of Youth found that, compared to nonuse or low use in adolescence, consistent or increasing patterns of marijuana use in adolescence are associated with an increased risk of obesity [10]. In another study among youth in the United States, frequent marijuana use was associated with overweight status but not obesity in young girls [11].…”
Section: Introductionmentioning
confidence: 69%
“…Waterreus et al (Waterreus et al, 2016) found that a significantly lower percentage of users than non-users were obese (53.7% of non-users, 36.7% of occasional users, and 28.7% of frequent users were obese (P < 0.001). Huang et al (Huang et al, 2013) studied three categories of adolescent Cannabis users; high users, sporadic users, and increasing users. Sporadic and high usage groups showed far lower obesity rates than low users (AOR for sporadic use = 0.2, for high use = 0.1).…”
Section: Results: Bmi Datamentioning
confidence: 99%
“…A recent study that analyzed population-based data of 7,084 community schoolchildren and adolescents showed that school level peer smoking was positively related to adolescent smoking, irrespective of socioeconomic status and background variables of responders [8]. Furthermore, in another study of 5,141 adolescents, an association was demonstrated between adolescence substance abuse and obesity (body mass index above 30) in young adulthood [9]. Growing concern about elevated blood pressure associated with obesity in young adults should be aimed at prevention of adult cardiovascular disease by healthy lifestyle counseling at early ages, as well as avoidance of other preventable risk factors (e.g.…”
Section: Venous Thromboembolism In Adolescents and Young Adults: Uniqmentioning
confidence: 99%